PERILAKU IBU TENTANG PEMANFAATAN POSYANDU ( POS PELAYANAN TERPADU ) BAGI BALITA DI DUSUN III DESA KLUMPANG KAMPUNG KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG TAHUN 2020 - KAMALIAH . (LP2MTBM MAKARIOZ, 2020)
The design of research on Maternal Behavior about the Utilization of Posyandu (Integrated Service Post) for Toddlers InDusun III Klumpang Village, Perak Kabupataen Deli Serdang Sub-District In 2020 is descriptive in the form of observationand the approach used is Cross Sectional. The population in this study was all mothers who had toddlers as many as 62respondents, The sample in this study was using the total sampling of all mothers who had toddlers as many as 62respondents. From the results of the study obtained from 62 respondents, a well-knowledgeable majority of 32 respondents(51.7%), and a knowledgeable minority of 11 reponden (17.8%), a positive majority of 47 respondents (75.8%) and a minorityof negative respondents (24.4%). the majority of the 51 respondents (82.2% ) and mothers who did not take action (17.8%).the majority of mothers were 35 respondents (56.4%), mothers with less behavior as much as 12 respondents (19.4%). It isrecommended for mothers who have toddlers to be more active in visiting, seeking information and listening to anycounseling provided by health workers to increase knowledge especially about posyandu.